Digitization of Sustainable Smallholder Oil Palm Plantations Towards Modern Oil Palm Cooperatives. Issue 1 (March 2021) - Hariyadi; Purwanto, M Y J; Falatehan, A F; Sukoco, H; Sembiring, W K
Abstract: Based on palm oil producers in Indonesia, private plantations are the largest national producers (54%), followed by smallholders (39%) and state-owned plantations (7%). In managing smallholder oil palm still have limited access to technology, production facilities, institutions, and marketing. With the system of digitizing sustainable smallholder, it is designed to transform the business processes carried out by oil palm farmers who join cooperatives into digital work patterns while still providing a permanent role and appreciation for their work from farmers and for farmers. The research was carried out in the KUD Tunas Muda, Teluk Merbau Village, Dayun District, Siak Regency, Riau Province, and was planned for three years. In the first year, the research objectives were to socialize the digital system; identification of smallholder oil palm plantation production factors; and record assistance in the implementation of input-output. The socialization activities showed that most farmers (80%) were very enthusiastic about this program. Farmers understand the factors that affect FFB production. Assistance in recording the implementation of inputs and outputs for smallholders is carried out to representatives of farmer groups using laptops or computers.